Implementasi Tanggungjawab Pemerintah Daerah Dalam Penanggulangan Penyakit HIV/AIDS di Daerah Kabupaten Lombok Timur - Putra, Guruh Sirgantera (Syntax Literate, 2019)
Communicable diseases that become long-term national development priorities 2005-2025 is malaria, dengue fever, diarrhea, polio, filaria, leprosy, pulmonary tuberculosis, HIV/AIDS, pneumonia, and other diseases that can be prevented by immunization. Although infectious diseases are a priority target of the prevention and eradication of the Millennium Development Goals (Millennium Development Goals) is the dengue hemorrhagic fever ( DHF ), malaria and tuberculosis, but in the area of East Lombok district HIV / AIDS is also urged to be eradicated, as has been become a plague that claimed the lives of hundreds of people every year. This study aims to determine how the spread of HIV/AIDS and the efforts of local authorities in tackling HIV/AIDS. The method used is a qualitative, descriptive analysis method, in checking the validity and reliability of the data used triangulation of researchers. Implementation Responsibility of Local Government in tackling infectious diseases HIV/AIDS in East Lombok district can not fully support the achievement of health development goals, namely realize the degree of public health as high, as a result there are still many obstacles that could potentially hinder efforts to control infectious diseases HIV/AIDS. Theoretic approach in the prevention of infectious diseases HIV/AIDS ternayata should be supported by lawmakers thoughtful, orderly and dignified, and behave as a "servant of the State" and "public servant". In the mechanism of implementation and monitoring of environmental management, the implementation process should be used as a final series of round setting, planning and implementation of a system of law. Thus the difficulties in implementing the surveillance and prevention of infectious disease of HIV/AIDS is the level of public awareness of the law is still low, regulation is not yet complete, the level of ability of law enforcement are low, and the cost ranges shopping. These factors must be considered in order to avoid violation of health laws. In addition to the effectiveness of supervision and control of infectious diseases, especially HIV/AIDS, then the law must be established in accordance with the need to prevent transmission of infectious diseases HIV/AIDS.Kata Kunci: Responsibility of local government, the spread of disease, HIV/AIDS